Prevalence of hypertension and its association with overweight and physical activity in adolescents - Lima, Alaine Souza (2014)
Introduction: Arterial hypertension (AH) is a chronic disease and it is considered as a public health problem. Objective: To determine the prevalence of AH and evaluate its association with overweight and physical activity in adolescents from the city of Petrolina (PE). Methods: It was a cross-sectional study of 305 adolescents between 12 and 17 years. Initially, sociodemographic data were collected and the measurements of weight, height and blood pressure were realized. A questionnaire of habitual physical activities for adolescents was used. To verify possible associations it was used the Fisher’s exact test. In all analyzes, was adopted a significance level of p<0.05. Results: The AH was found in 1% (95%CI 0.21–2.89) of adolescents, all male. Overweight was found in 16% of the sample, of these 15.4% were girls and 17.4% were boys. There was no association between hypertension and body mass index (BMI) (p=0.408) and AH and physical activity (p=0.245). Conclusion: It can be concluded that the sample studied showed low prevalence of AH, showed no association with excess weight and physical inactivity.